Identification of CO Exposure, Habits, COHb Blood and Worker's Health Complaints on Basement Waterplace Apartment, Surabaya - Intan Retno Dewanti (Universitas Airlangga, 2018)
Carbon monoxide (CO) is a silent killer because it is tasteless, colorless, odorless, and causes of death. In the basement, pollution level from vehicle engines combustion is higher than in the ambient air. Workers in the basement potentially expose to CO that trapped while they were working. CO inhaled will form COHb on the blood. This study aims to identify CO exposure, worker habits, COHb blood, and health complaints during their working time in the basement of apartment Waterplace Surabaya. This research was a descriptive with cross-sectional design and used purposive sampling technique with 20 respondents. Data which were collected through observation and interviews. The result showed that CO measurement was below 25 ppm standard. Most characteristics of workers were male (80.0%), 21–29 years old (55.0%), working time for â‰¤ 12 months (55.0%) and working hours for 12 hours (55.0%). The worker's habits mostly were smoking (80.0%), regularly consume fruit (55.0%) and vegetables (60.0%). The majority (90.0%) COHb level was above the 3.5% standard. Health worker complaints were dizziness (80.0%), impaired concentration (60.0%) and tired (55.0%) while their working time. Workers that smoking, eating fruits, and vegetables were having a blood COHb levels higher. It was concluded that the levels of CO gas below the standards while blood COHb above the standards. It was suggested to reduce smoking, to start a healthier lifestyle, and to use masker while their working time.